Sylvia Earle : deep sea explorer and ocean activist - White, Katherine, 1975- (New York : The Rosen Publishing Group, 2004)
Examines the personal life and professional career of Sylvia Earle, who is an oceanographer, marine botanist, ecological activist, aquanaut, and author.
Includes bibliographical references
Keywords: Earle, Sylvia A., -- Juvenile literature; Marine biologists. -- United States. -- Juvenile literature